Maternal Adiposity Influences Neonatal Brain Functional Connectivity - Salzwedel, Andrew P.; Gao, Wei; Andres, Aline; Badger, Thomas M.; Glasier, Charles M.; Ramakrishnaiah, Raghu H.; Rowell, Amy C.; Ou, Xiawei (Frontiers in Human Neuroscience, 2019)
The neural mechanisms associated with obesity have been extensively studied, but the impact of maternal obesity on fetal and neonatal brain development remains poorly understood. In this study of full-term neonates, we aimed to detect potential neonatal functional connectivity alterations associated with maternal adiposity, quantified via body-mass-index (BMI) and body-fat-mass (BFM) percentage, based on seed-based and graph theoretical analysis using resting-state fMRI data. Our results revealed significant neonatal functional connectivity alterations in all four functional domains that are implicated in adult obesity: sensory cue processing, reward processing, cognitive control, and motor control. Moreover, some of the detected areas showing regional functional connectivity alterations also showed global degree and efficiency differences. These findings provide important clues to the potential neural basis for cognitive and mental health development in offspring of obese mothers and may lead to the derivation of imaging-based biomarkers for the early identification of risks for timely intervention.